A new species of Marasmius Sect. Neosessiles (Basidiomycota, Agaricales) from the artificial Dipterocarpaceae forest in Indonesia - Atik Retnowati; Jaya Seelan Sathiya Seelan (College of Life Science, National Taiwan University & Biodiversity Association of Taiwan, Taiwan, 2022)
Marasmius jasingensis (Agaricales, Marasmiaceae), is described as a new species from Haurbentes, the artificial Dipterocarpaceae forest in West Java, Indonesia. The new species is distinguished by having a small basidiomata with orbicular, pale orange pileus, distant lamellae, a stipe being absent or rudimentary, Rotalis-type cheilocystidia, pleurocystidia, and pileipellis cells. Morphologically, it is similar to M. sejunctus, M. conchiformis, M. spaniophyllus Berk., M. sessiliaffinis and M. griseoroseus. Comprehensive descriptions, illustrations, and comparisons with similar taxa are presented.